Isolation and characterization of exosomes from bovine milk - Kankaanpää, Santeri (My University, 2019)
Exosomes are extracellular vesicles of endosomal origin with a diameter of 30-150 nms that contribute to cell to cell communication and may be involved in interspecies communication on the nano-level. Exosomes contain wide array of bioactive components from micro RNAs to proteins and bioactive lipids. Milk is a unique platform of information from mother to infant in mammals with unique content of growth factors and immunogens. Some of these messages of biological programming can be transferred via exosomes. Bovine milk contains vesicles of all sizes in very high concentrations. The abundance of vesicles in milk provides a platform for commercial scale purification of bioavailable extracellular vesicles, including exosomes. Isolation of exosomes from such complex media as milk provides challenges with high fat and protein content with similar physiochemical properties as milk exosomes. Here we demonstrate an efficient protocol for isolation of milk exosomes with the use of differential centrifugation followed by secondary purification with size exclusion chromatography or sucrose gradient centrifugation. Resulting samples were analysed for exosome enriched proteins with western blot for ALIX, TSG101 and CD81. Further analysis was done with mass spectrometry to identify the complete protein profile of isolated vesicles that included also exosomal marker proteins HSC70, CD81 and CD9.
Keywords: Exosomes, western blot, bovine milk, mass spectrometry, chromatography